Practical Realism: Against Standard Scientific Realism and Anti-Realism - Vihalemm, Rein (Studia Philosophica Estonica, 2013)
In this paper, the elaboration of the concept of practical realist philosophy of science which began in the author's previous papers is continued. It is argued that practical realism is opposed to standard scientific realism, on the one hand, and antirealism, on the other. Standard scientific realism is challengeable due to its abstract character, as being isolated from practice. It is based on a metaphysical-ontological presupposition which raises the problem of the God's Eye point of view (as it was called by Hilary Putnam). Joseph Rouse's conception of science as practice, Sami Pihlström's pragmatic realism, and even Ilkka Niiniluoto's critical scientific realism are interpreted as practical realist conceptions. Pihlström suggests that the contemporary scientific realist should be prepared to accept the pragmatically naturalized Kantian transcendental perspective on realism. It is argued, however, that this realistically naturalized Kantianism can be nothing more than practical realism, as originated by Karl Marx.